What is the digital economy, and how to measure it - Gumah, Mohamed E.; Jamaludin, Zulikha (2006)
This paper presents the main elements of digital economy and the measurement of it.Firstly n gives a general idea about general economy by presenting a short definition of digital economy and the main issues concerning it.Then, the paper presents the measurement of digital economy by three different methods and discusses their results.